INNOVATIONS IN THE RETAIL SEGMENT OF BANKING ACTIVITIES IN UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This thesis examines the impact of innovations on the development and structure of the retail banking business. The modern stage of banking service development, taking place under conditions of increasing competition and crises in the global financial market, is characterized by three main trends: the growing role of innovative technologies, an increase in the volume and variety of retail banking services, the formation of new segments in the customer service market.